2009
DOI: 10.1042/bj20090785
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of endoplasmic reticulum stress stimulate lipid droplet formation in Saccharomyces cerevisiae

Abstract: LDs (lipid droplets) are cellular organelles which can be found in nearly all eukaryotic cells. Despite their importance in cell biology, the mechanism underlying LD biogenesis remains largely unknown. In the present study we report that conditions of ER (endoplasmic reticulum) stress stimulate LD formation in Saccharomyces cerevisiae. We found that LDs accumulated in yeast mutants with compromised protein glycosylation or ER-associated protein degradation. Moreover, tunicamycin and Brefeldin A, agents which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 36 publications
5
136
0
Order By: Relevance
“…Concurrent with increased lipogenesis, some adipogenic proteins were elevated in liver tissue [FAS, PPAR ␥ , and stearoyl-CoA desaturatase-1 (SCD1)], while others (SREBP-1c, DGAT, and ACC1) did not change. The level of microsomal TAG transfer protein, which facilitates the stress result in an increase in droplet number ( 69 ). However, the morphology of droplets under the two conditions is very different.…”
Section: Lipid Homeostasismentioning
confidence: 99%
“…Concurrent with increased lipogenesis, some adipogenic proteins were elevated in liver tissue [FAS, PPAR ␥ , and stearoyl-CoA desaturatase-1 (SCD1)], while others (SREBP-1c, DGAT, and ACC1) did not change. The level of microsomal TAG transfer protein, which facilitates the stress result in an increase in droplet number ( 69 ). However, the morphology of droplets under the two conditions is very different.…”
Section: Lipid Homeostasismentioning
confidence: 99%
“…Previous reports have indicated that the ER-stress inducer tunicamycin increases LD levels in yeast (Fei et al, 2009) and in human hepatoma cells (Lee et al, 2012). These implicate core in increasing the number of LDs in response to ER stress in a manner similar to tunicamycin.…”
Section: Figmentioning
confidence: 99%
“…1,2 LDs play a key role in lipid homeostasis. However, recent findings suggest that LDs have many other functions; they play roles in protein degradation 3,4 and the endoplasmic reticulum (ER) stress response, 5 they act as sites for assembly of infectious virions, 6 are involved in membrane trafficking and signal transduction, and act as a temporary storehouse of proteins. 1,7,8 Understanding LD homeostasis, biogenesis and catabolism is critical for understanding the pathophysiology of lipid storage disorders like obesity, lipodystrophy (abnormal distribution of fat), type2-diabetes, insulin resistance, atherosclerosis and its associated diseases.…”
mentioning
confidence: 99%